Prototipe Pengukur Suhu dan Pengontrol Kelembaban pada Tanaman Hidroponik Menggunakan Blynk Android - Hasibuan, Johannes Ganda Setianto; Novadi, Iqbal; Rivai P, Agung Wibisono (LPPM Universitas Negeri Jakarta, 2020)
The final project aims to make Prototype Temperature Measuring and Humidity Control in Hydroponic Plants Using Blynk Android. The research method uses the method of making Prototyping. Making prototypes begins with gathering needs, building prototyping, evaluating prototyping, coding the system, testing the system and evaluating the system. Prototype of Temperature Measuring and Humidity Control in Hydroponic Plants Using Blynk Android, which uses a DHT22 sensor to measure temperature, and a Soil Moisture sensor to measure Water Moisture in Hydroponic plants, and the NodeMCU ESP8266 as the process. There is a 2 Channel Relay which is where to activate the Water Pump. Based on the results of Prototype Testing of Temperature Measuring and Humidity Control in Hydroponic Plants Using Blynk Android that researchers have done has been successfully created and has been tested to measure the state of ambient temperature and measure water humidity in hydroponic plants. When the DHT 22 sensor reads the temperature state, it will send data to Blynk. The Soil Moisture sensor reads the humidity in the hydroponic plant, it will be displayed on the blynk, if it is dry it will turn on the relay and activate the water pump. Penelitian ini bertujuan untuk membuat Prototipe Pengukur Suhu dan Pengontrol Kelembaban pada Tanaman Hidroponik Menggunakan Blynk Android. Metode Penelitian menggunakan metode pembuatan Prototyping. Pembuatan prototipe di awali dengan melakukan pengumpulan kebutuhan, membangun prototyping, evaluasi prototyping, mengkodekan sistem, menguji sistem dan mengevaluasi sistem. Prototipe Pengukur Suhu dan Pengontrol Kelembaban pada Tanaman Hidroponik Menggunakan Blynk Android, yang dimana menggunakan sensor DHT22 untuk mengukur suhu, dan sensor Soil Moisture untuk mengukur Kelembaban Air dalam tanaman Hidroponik, Serta NodeMCU ESP8266 sebagai prosesnya. Terdapat Relay 2 Channel yang dimana untuk mengaktifkan Pompa Air. Berdasarkan Hasil Pengujian Prototipe Pengukur Suhu dan Pengontrol Kelembaban pada Tanaman Hidroponik Menggunakan Blynk Android yang telah peneliti lakukan sudah berhasil dibuat dan sudah diuji dapat mengukur keadaan suhu sekitar dan mengukur kelembabanr air dalam tanaman hidroponik. Ketika sensor DHT 22 membaca keadaan suhu, maka akan mengirimkan data ke Blynk. Sensor Soil Moisture membaca keadaan kelembaban di tanaman hidroponik, maka akan di tampilkan di blynk, jika dalam keadaan kering makan akan menyalakan relay dan mengaktifkan pompa air.